The pass through of monetary policy to euro area bank interest rates - Nektarios Michail; Kyriaki Louka (German Economic Review (GER), 2025)
We examine the transmission of monetary policy to bank interest rates in the euro area, using a rolling estimation. The results, using various fixations for the Euribor rate and different maturities for bond yields, suggest that the pass through of policy rates to bank interest rates was relatively stable prior to the use of unconventional monetary policy measures. After the use of unconventional policies, the pass-through multiplier from the Euribor rate and the short-term bonds increased, while the pass-through from longer-term bonds markedly decreased. It appears that unconventional monetary policy operations allow for bank lending rates to further decline, which could lead to higher lending, with potential financial stability issues arising. In addition to the excess liquidity created by asset purchases, factors such as credit risk and house price growth also appear to impact the pass through.
Keywords: 330; asset purchases; bank interest rates; deposit beta; Euro area; monetary policy; pass through